(untitled) (Journal of Economic Research & Business Administration, 2016)
The article deals with modern methods for the determination of market prices for export of Kazakh cotton fiber, the factors are influencing on the formation of prices. The processes connected with pricing in the world trade market are analyzed and also the factors influencing pricing of the general and applied view are presented. The price of cotton is affected by such factors as: the oil price, affecting the price of synthetic fibers; prices for grains and soybeans as a substitute crops replacing cotton from farmers at higher market demand; economy and politics as well as the world in a single country; weather conditions affecting the crop. This article gives an analysis of the processes related to pricing on the world cotton market. In this article analyze the process of formation of cotton prices in the world market. The article also analyzes the problems and prospects of development of the cotton sector in Kazakhstan. The article presents the proposal and guide research aimed at improving the conditions of cotton sphere in Kazakhstan